Process Performance and Biogas Output: Impact of Fluctuating Acetate Concentrations on Methanogenesis in Horizontal Anaerobic Reactors - Tongco, Jovale Vincent; Jannat, Md Abu Hanifa; Kim, Sangmin; Park, Sang Hyeok; Hwang, Seokhwan (Energies (Basel), 2025)
The influence of introducing fluctuations in acetate feeding concentrations on the process stability of a lab-scale horizontal anaerobic reactor (HAR) was investigated to ascertain its effects on acetoclastic methanogenesis. Acetate concentrations were randomized at 85 g COD/L ± 20% and discontinuously fed in the duplicate HARs for five days per week (giving the system time to rest and equilibrate for two days). The reactors were monitored daily with respect to performance indicators (physicochemical variables). The residual acetate concentration was observed to fluctuate at the initial stages, followed by a converging trend (decrease in variance) until the end of operation. Furthermore, letting the system self-neutralize and equilibrate during rest days resulted in improved process performance. The daily acetate degradation efficiency at ~90% and methane concentration at ~60% were attained after operating the reactors for 80 days. The results divulged that introducing fluctuations in acetate feeding concentrations does not affect the stability of biogas production and methane concentration. The acclimatization of the methanogenic population (predominantly Methanosaeta, then shifting to Methanosarcina) was also observed.